PROGRAM ADVOCACY AND PUBLIC AWARENESS OLEH UNDER THE SAME SUN (UTSS) DALAM MELINDUNGI HAK ASASI MANUSIA ORANG-ORANG ALBINO DI TANZANIA - Putri GW, Maria Triana; Fasisaka, Idin; Parameswari, A.A Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT Under The Same Sun as an international organization committed to the Human Rights protection of people with albinism have been instrumental in handling the issue of discrimination against people with albinism in Tanzania. This study attempts to analyze the involvement of UTSS in dealing with problems of discrimination against people with albinism in Tanzania through Advocacy and Public Awareness Program. This research used descriptive qualitative research methods by using the concept of Human Rights NGOs and advocacy. Both of those concepts was able to explain the role of UTSS as a Human Rights NGOs in addressing discrimination against people with albinism in accordance with the commitment of these organizations through Advocacy and Public Awareness Program. These Program are elaborated into four advocacy activities namely Understanding Albinism Seminars, leaflets dissemination, documentary film screenings, and the implementation of international advocacy.                                                           Keywords : Under The Same Sun, discrimination of people with albinism, Advocacy and Public Awareness Program, Tanzania.